Augmented Reality in Construction: Enhancing Efficiency and Collaboration - Bahir Abdul Ghani (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Augmented Reality (AR) and Mixed Reality (MR) technologies are revolutionizing the construction industry by transforming traditional document-based practices into model-based information management systems. The integration of these technologies has demonstrated substantial improvements in project execution, collaboration, and training processes across various construction sectors. Through integration with Building Information Modeling (BIM), AR/MR systems enable enhanced visualization, coordination, and real-time decision-making capabilities. These technologies have proven particularly effective in structural work, mechanical installations, and architectural finishing phases, where precise spatial comprehension is crucial. The implementation spans multiple applications, including progress monitoring, quality inspection, safety management, and productivity enhancement. While technical challenges exist, particularly in outdoor construction environments, successful implementations have shown marked improvements in communication efficiency, error reduction, and knowledge transfer between experienced and novice professionals. The adoption of AR/MR represents a significant step toward digital maturity in construction, with standardized implementation frameworks emerging to guide organizations in effective deployment.